Steinbeck Family Beach Picnic in Monterey, California - unknown:::Creator::::::::::::
An inscription on the back reads: 'Beach picnic, [John Steinbeck] in his mother's [Olive's] lap, father [John Ernst] 2nd to right, sisters Esther and Elizabeth (bareheaded) standing behind. Mrs. E. G. Ainsworth; Salinas Library."